MICROMETER-SCALE CAVITIES IN FIBROUS AND CLOUDY DIAMONDS - A GLANCE INTO DIAMOND DISSOLUTION EVENTS - Klein-BenDavid O.; Wirth R.; Navon O. (My University, 2007)
Micrometer sized internal cavities in diamonds preserve evidence of diamond dissolution events. Combining the methods of focused ion beam (FIB) sample preparation and transmission electron microscopy (TEM) enables these features to be studied in detail. Micrometer-scale cavities are found in the inner parts of fibrous and cloudy kimberlitic diamonds. Their filling consists of amorphous matrix, secondary nano-crystals, volatiles and in some cases larger resorbed crystals. Trapped minerals include corundum, Kappa-alumina, quartz, olivine, moissanite-6H and Ca-Mg carbonates. This is the first observation of Kappa-alumina in nature. Secondary nano-minerals are observed within the amorphous matrix and include carbonates, Al-oxide, fluorite, ilmenite and secondary diamond crystals. The amorphous matrix is spongy and its composition is dominated by amorphous carbon, nitrogen, chlorine and also contains water. When no crystalline phases are observed, the matrix is also enriched in alumina, silica and in some cases calcium. We propose that micrometer scale cavities in diamonds form during dissolution events induced by the introduction of oxidizing hydrous fluids into the diamond growth area. Hydrous fluids are the main dissolving agents for most kimberlitic diamonds [Fedortchouk, Y., Canil, D., Semenets, E., 2007. Mechanisms of diamond oxidation and their bearing on the fluid composition in kimberlite magmas. Am. Mineral. 92, 1200-1212]. At diamond forming conditions silica and alumina are enriched in hydrous fluids that are in equilibrium with eclogites [Kessel, R., Ulmer, P., Pettke, T., Schmidt, M.W., Thompson, A.B., 2005. The water-basalt system at 4 to 6 GPa: Phase relations and second critical endpoint in a K-free eclogite at 700 to 1400 °C. Earth Planet. Sci. Lett. 237, 873-892]; this is consistent with the increased solubility of alumina with increased pressure and temperature in the Na-Cl bearing fluids [Manning, C.E., 2006. Mobilizing aluminum in crustal and mantle fluids. J. Geochem. Explor. 89, 251-253; Manning, C.E., 2007. Solubility of corundum + kyanite in H2O at 700C and 10 kbar: evidence for Al-Si complexing at high pressure and temperature. Geofluids. 7, 258-269]. Additionally, hydrous fluids may leach grain boundaries that are enriched in alumina in peridotitic environments [Hiraga, T., Anderson, I.M., Kohlstedt, D.L., 2004. Grain boundaries as reservoirs of incompatible elements in the Earth's mantle. Nature. 427, 699-703; Wirth, R., 1996. Thin amorphous films (1-2 nm) at olivine grain boundaries in mantle xenoliths from San Carlos, Arizona. Contrib. Mineral. Petrol. 124, 44-54]. Diamond dissolution will form oxidized carbon species and may decrease the solubility of silica and alumina in the dissolving agent leading to their precipitation. Diamond forming fluids that are trapped in sub-micrometer inclusions in the same fibrous diamonds are the dominant fluid component in the diamond growth area. Corrosive hydrous fluids are less common and appear as short, discrete events, followed by the return of the common diamond forming fluids and continued diamond precipitation. © 2007 Elsevier B.V. All rights reserved.
Keywords: AL-RICH ASSEMBLAGES; AMORPHOUS MATRIX; DISSOLUTION CAVITIES; HYDROUS FLUIDS; KAPPA-ALUMINA; MOISSANITE